The Crisis of Japanese Higher Education: Where Is the Problem? Review of: Where Is the Problem? (Asian Education Studies, 2017)
In this recently published book, Shunya Yoshimi discusses the controversy in Japanese higher education stirred by a request from the government sent in June 2015 to all national universities asking them to shut down their humanities and social sciences departments. Various media and intellectuals inside and outside of Japan immediately reacted and criticized the request of the government. The author carefully explains the details of how the controversy was stirred up. He also notes that although the news came as a shock because of inadequate treatments of media, is not abrupt but is part of the reform of national university system that begun in 1990s (such as loosening of the standards for university establishment and turning national universities into independent administrative entities), and further that the disparagement of humanities and social sciences has almost always existed since the birth of universities in Japan.